The Strange Case of a Broken Periodontal Instrument Tip - Manuela E. Kaufmann; Alex Solderer; Deborah Hofer; Patrick R. Schmidlin (MDPI AG, 2020)
This case report describes a rare case of a broken periodontal probe tip and its removal. A male patient presented himself in June 2019 due to a painful tooth in the upper left quadrant. The patient elected treatment in the dental school's student course. In October 2019, in preparation for full-mouth rehabilitation, a complete diagnostic status was performed, including radiographs. In this context, a metal-dense fragment was identified in the apical region of the (missing) tooth 45. It was diagnosed as the broken tip of a periodontal probe (type AE P OWB). Since a PCP-12 probe is generally used in-house, iatrogenic damage during the initial examination or student course could be excluded a priori. The patient was not able to remember any treatment that could be associated with the instrument's breaking. Since the probe fragment was palpable and a translocation could not be precluded, the patient agreed to its removal under local anesthesia, after a cone-beam CT. This article describes and discusses this particular case, with special emphasis on iatrogenic instrument fractures and their removal.